Exploring speech acts in Instagram reels: An implication for English language learning - Nur Swarnadani; Nina Sofiana (English Learning Innovation, 2026)
Social media has increasingly become an informal platform for English learning, with Instagram Reels emerging as an engaging medium for short-form educational content. While previous studies have focused on linguistic outcomes such as vocabulary and speaking skills, the pragmatic dimension of learning through short videos remains underexplored. This study aims to classify the types of speech acts used in educational Instagram Reels created by @englishwithlucy and explain how these acts contribute to English learning in digital contexts. This research employed a qualitative descriptive design, with fifteen Reels uploaded between January and May 2025 selected through purposive sampling. A total of 170 instructional utterances were transcribed and analyzed using Searle’s (1976) Speech Act Theory. Data were examined through content-based pragmatic coding and frequency calculation, followed by category validation to ensure coding consistency. The findings show that assertive acts (58.82%) are the most frequently used, followed by directive acts (35.29%), while expressive and commissive acts occur minimally, and declarative acts are absent. These results suggest that the videos emphasize explanation and interactive guidance to support micro-learning and develop communicative competence. The study provides implications for teachers and content creators in designing concise and engaging English learning materials on digital platforms.